Revitalisasi Teknologi Informasi pada Sistem Informasi Kepegawaian Universitas Muhammadiyah Bengkulu Menggunakan COBIT 4.1 - Fernandez, Sandhy; Marhalim, Marhalim (UNIVED Press, 2019)
Information technology greatly influences personnel activities in particular and is currently one of the resources in universities to manage data well, increase effectiveness and efficiency in the service process. This research aims to measure the maturity level of personnel information system governance, especially the Delivery and Support domain. This measurement method uses Cobit (Control Objective for Information and Related Technology). Calculation of the maturity level of selected processes based on the Bengkulu Muhammadiyah University Strategic Plan was carried out by analyzing based on the level of importance of the personnel information system, questionnaire identification was carried out using the Raci Chart. With this research, it is known that the maturity level of personnel information system governance is at maturity level 2, to be used as a recommendation for adjustments to increase to level 3